Pembaruan Kebijakan Publik: Menuju Kebijakan Berbasis Prakarsa Masyarakat - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Abstract The backbone of the decentralization and democratization process in Indonesia is transforming to bring about participatory policy-making. In recognition of the degree of institutionalization left behind by the previous centralized authoritarian policy-making of the New Order Government, this article aims to identify the challenges that lie a head.